An effective federal climate change act needs leading indicators - Daniela Fietze; Mats Kröger; Thorsten Müller; Karsten Neuhoff (DIW Weekly Report, 2021)
To reach the climate targets, the course towards a climate-neutral society must be set now. However, the current monitoring instruments in the Climate Change Act do not provide sufficient information to policymakers and society on the effectiveness of policy instruments and programs, as they focus exclusively on greenhouse gas reduction targets, which are subject to uncertainty. Moreover, they only allow developments to be identified with a delay and map transformative measures inadequately. The Climate Change Act should be supplemented with leading indicators to address these deficits. By providing a broader information base, leading indicators could help improve the implementation of energy and climate policy measures.
Keywords: H11; K32; L51; O2; 330; Intermediary Indicators; Climate Policy; Climate Neutrality; Policy Monitoring; Climate Governance